Thirty-Day Hospital Readmissions for Granulomatosis With Polyangiitis in the United States: A Nationwide Analysis. Issue 5 (August 2020) - Luo, Yiming; Jiang, Changchuan; Arevalo Molina, Ana Belen; Murray, Shane; Anez, Gustavo Contreras; Salgado, Maria; Xu, Jiehui
Abstract : Background/Objective: Granulomatosis with polyangiitis (GPA) is a systemic necrotizing vasculitis that often results in frequent hospitalizations. We investigated the characteristics and predictors of 30-day hospital readmissions in GPA. Methods: We performed a cross-sectional analysis using the 2014 National Readmission Database. We included nonelective admissions with a primary or secondary diagnosis of GPA. We compared characteristics between readmissions and nonreadmissions. Independent predictors for readmissions were studied using mixed-effects multivariable logistic regression. Results: We evaluated a total of 9749 hospital admissions with GPA, among which there were 2173 readmissions (22.3%) within 30 days of discharge. The top 5 primary reasons for readmissions were GPA, sepsis, pneumonia, acute respiratory failure, and acute kidney injury. Granulomatosis with polyangiitis readmissions were associated with higher length of stay (8.0 vs 7.2 days; p = 0.019) and less discharge home (50% vs 63%, p < 0.001). Independent predictors for readmissions were younger age (odds ratio [OR], 0.99; p = 0.013), no private insurance (OR, 0.50; p < 0.001), higher Charlson Comorbidity Index (OR, 1.12; p = 0.039), congestive heart failure (OR, 1.71; p = 0.001), acute kidney injury (OR, 1.39; p = 0.005), and discharge to home health care (OR, 1.29; p = 0.039). Conclusions: We found a significant burden of 30-day readmissions among GPA populations. Clinicians should be vigilant regarding patients with high risk of readmissions, including those with younger age, public insurance, higher comorbidity burden, cardiac and renal complications, and unfavorable discharge dispositions. Abstract : In this study, the authors aimed at determining the risk factors for re-admission to the hospital for patients with granulomatosis with polyangiitis (GPA) using the 2014 national readmission database. There were 9749 admissions for GPA and 2173 readmissions. Younger age, lack of private insurance, higher Charlson comorbidity index, acute renal failure and discharge to home health care were found to be predictive of readmissions in these GPA patients. Preliminary study were reassuring and thus the actual trial could take place.Supplemental digital content is available in the text.